(3efThQ GdTjN GdYGdi GdWGgQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe GdEdg GdbGOQ hef bQH CLd GdfGcK GdcGaQ CWGd Gdgd HbGA GdTjN GdaGVd bO EJSYJ WQb GdeXGde s
(3BNQgG (B:s
(3adG jVLY GdTjN ai EfaGP cJGH ai GdJQJjH Hbhdg eZdb HJUMjM GdadL hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B94s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds